2013
DOI: 10.1002/emmm.201302797
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification and functional analyses of microRNA signatures associated with cancer pain

Abstract: Cancer pain remains a major challenge and there is an urgent demand for the development of specific mechanism-based therapies. Various diseases are associated with unique signatures of expression of microRNAs (miRNAs), which reveal deep insights into disease pathology. Using a comprehensive approach combining genome-wide miRNA screening, molecular and in silico analyses with behavioural approaches in a clinically relevant model of metastatic bone-cancer pain in mice, we now show that tumour-induced conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 66 publications
3
73
0
6
Order By: Relevance
“…Conditional deletion of Dicer, a central enzyme in miRNA processing, in DRG sensory neurons leads to deficits in inflammatory pain (Zhao et al, 2010). miRNA expression profiling study in DRG tissue identified 63 and 57 miRNAs whose expression is significantly altered after neuropathic pain (von Schack et al, 2011) and metastatic bone-cancer pain model (Bali et al, 2013). Furthermore, upregulation of spinal miR-124 or miR-103 is reported to prevent and treat persistent inflammatory and neuropathic pain (Favereaux et al, 2011;Willemen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conditional deletion of Dicer, a central enzyme in miRNA processing, in DRG sensory neurons leads to deficits in inflammatory pain (Zhao et al, 2010). miRNA expression profiling study in DRG tissue identified 63 and 57 miRNAs whose expression is significantly altered after neuropathic pain (von Schack et al, 2011) and metastatic bone-cancer pain model (Bali et al, 2013). Furthermore, upregulation of spinal miR-124 or miR-103 is reported to prevent and treat persistent inflammatory and neuropathic pain (Favereaux et al, 2011;Willemen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the tumor-induced upregulation of miR-146a and miR-183 in sensory neurons markedly attenuates tumor-mediated hyperalgesia (Li et al, 2013). In contrast, augmenting the expression of miR-370 in DRGs leads to exaggerated tumor-mediated hyperalgesia (Bali et al, 2013). These findings demonstrate miRNAs as key regulators of physiologic and pathologic processes underlying chronic pain and suggest that specific miRNAs may act as new molecular targets for pain prevention and relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that the differences found across different pain models suggest the existence of disorder specific miRNAs rather than common miRNA regulators of nociceptive modulation. For example, members of the miR-34 family are strongly underexpressed following neuropathic pain induction while appears highly overexpressed following bone metastatic pain induction in DRG [85,86]. Also, it has been described that the interactions between sensory neurons and non-neuronal cells such as immune cells and microglia modulate nociceptive sensitivity [87] and therefore changes in other cells of the body, such as blood cells, might be indicators of individual changes in nociceptive thresholds, even if the alteration pattern of the deregulated microRNAs does not match with that in the tissue affected they might still serve as reporters.…”
Section: Mt Impact On the Nervous System And On Pain Reliefmentioning
confidence: 99%
“…It has been reported that approximately one-third of patients who are actively receiving treatment for cancer, and two-thirds of those with advanced malignant disease experience pain (1). Cancer pain, particularly bone cancer pain, which is one of the most frequent symptoms in bone cancer patients (2), affects their quality of life, and current treatments are limited (3).…”
Section: Introductionmentioning
confidence: 99%